The Hybrid Contracts in Trade Finance and Letters of Credit Against Multipurpose Financing - Yustika Pratiwi, Hamlatussa’adah; Herdiana Abdurrahman, Nana; Prasetyo, Yoyok (Zona Law And Public Administration Indonesia, 2024)
The concept of "Hybrid Contract" in Islamic financial institutions refers to the combination or combination of two or more types of contracts or sharia agreements to achieve certain goals in accordance with sharia principles. In the context of Islamic banking, this refers to the use of more than one type of contract or financing mechanism in a single transaction to meet complex needs and requirements. Hybrid Contract in trade finance and Letter of Credit (L/C) multipurpose financing in sharia financial institutions refers to the combination or combination of two or more different types of sharia contracts or agreements to meet the needs of complex trade finance and multipurpose financing in the sharia context. This is a flexible approach that allows Islamic financial institutions to design financing solutions that comply with Sharia principles and the needs of their customers.